ANALISIS PENERAPAN SUPERVISI KEPALA SEKOLAH UNTUK MENINGKATKAN KUALITAS PENDIDIKAN: Penelitian di SMP Negeri 2 Cimenyan Kabupaten Bandung - Teguh Prayitno (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2022)
The purpose of supervising education carried out by the principal is to help teachers in schools to be able to carry out their duties as educators and teachers to the maximum to create a better learning situation. This research is quantitative research with descriptive methods. The technique of collecting data is observation, interview and documentation. While data analysis uses data reduction, played data and data harmony. The results of the study showed that a) The academic supervision program conducted at SMPN 2 Cimenyan Bandung Regency, consists of a series of activities initiated by determining supervision objectives, curriculum development, evaluation of learning devices, evaluation of teacher teaching methods, evaluation of learning activities, and development of student learning experiences. b) The implementation of supervision in this school is considered effective considering that the purpose of the implementation of supervision has been realized. The purpose of implementing the supervision is to achieve the development of teacher competencies, teachers are helped in developing the curriculum, teachers are able to develop MGMP (Subject teacher deliberation) activities, and teachers are helped to carry out Class Action Research (PTK). c) Supervision techniques carried out are: 1) Class visits, 2) School visits, 3) Impromptu exams, 4) Case conferences, 5) Document Observations, 6) Interviews, 7) Questionnaires, 8) Reports. d) Internal constraints in the implementation of academic supervision experienced by principals and teachers in increasing supervision including school quality competition are increasingly heavy. While external constraints include managing the demands of accountability from the higher society and follow-up supervision of the principal consists of fostering a learning process that includes direct coaching and indirect coaching. The next follow-up activity is the stabilization of academic supervision instruments, which include fostering the learning process and stabilizing supervising instruments.